Low-cost, abundant binary sulfides as promising thermoelectric materials. Issue 4 (May 2016) - Ge, Zhen-Hua; Zhao, Li-Dong; Wu, Di; Liu, Xiaoye; Zhang, Bo-Ping; Li, Jing-Feng; He, Jiaqing
Abstract : In the past several years, metal sulfides have been the subject of extensive research as promising thermoelectric materials with high potential in future commercial applications due to their low cost, low toxicity, and abundance. This review summarizes recent developments and progress in the research of metal sulfides, particularly for binary metal sulfides such as Bi2 S3, Cu2− x S, and PbS. Methods for improving the thermoelectric properties of these binary sulfides are emphasized, and promising strategies are suggested to further enhance the thermoelectric figure of merit of these materials.